Ft-Ir And Edxrf Analysis Of Wall Paintings Of Ancient Ainos Hagia Sophia Church - Başaran, Sait; Kocabaş, I.; Güleç, A.; Çeşmeli, H.; Uçar, B.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
The wall paintings of ancient Ainos Hagia (Saint) Sophia Church were investigated by FT-IR and EDXRF spectroscopy. Calcite, aragonite, gypsum, and quartz were detected in all the samples. Feldspar phases and pigments were inferred from both band component analysis and the second derivative profiles of the IR spectra. The black, dark brown, and red colouration was due to different concentrations of MnO2, Mn2O3, magnetite, and haematite. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ancient Wall Paintings; Archaeometry; EDXRF; İnorganic Pigments; IR Spectroscopy; Raman; Ceramics; Pottery; Antik Duvar Resimleri; Arkeometri; İnorganik Pigmentler; Seramikler; Çanak Çömlek